In Europe we trust? - Jo Ritzen; Jasmina Haas (Institute for the Study of Labor (IZA), 2016)
The decrease in the rule of law and in control of corruption in several EU countries is a threat to the cohesion in the EU. Brexit has reinforced the centrifugal forces in the EU. To counter this threat the EU needs to engage in unpopular measures as they infringe on the Member States' sovereignty. We propose to introduce new measures in treaty revisions like the possibility of individuals to appeal to European courts to counter negative developments in governance in EU Member States.
Keywords: D02; D72; D78; E02; I31; K20; K33; O43; O52; 330; governance; institutions; EU; economic growth